Early Byzantine Apocalyptic Discourses : Coping with Crises in the Sixth and Seventh Centuries - Strickler, Ryan W., (Brill's Series on the Early Middle Ages ;, 2026)
The Byzantine Empire faced many threats, but few were as great as the events of the sixth and seventh centuries, when paranoia, plagues, and wars threatened to tear the empire apart. Like today, prophets predicted horrors to come while preachers called on their congregations to repent. This book considers how the Byzantines understood the crises of the period and their role in divine history by reframing their troubles through an apocalyptic lens. While most scholars have interpreted these messages as a prediction of the end, this book argues for a different reading, understanding them instead as messages of hope.